(untitled) (Research, Society and Development, 2025)
Body image is characterized by cognitive understanding, which combines with various reflections on body aesthetics. With this characterization, the objective of this study is to identify the self-image of elderly subjects who practice physical exercise. The study with a sample of 84 elderly people, 68 women and 16 men aged between 60 and 79 years (CI: 95%, p<0.05) frequent the Open University of Third Age (UATI-USP) and Open University of Terceira Age (UATI-FESC) used Steglich’s self-image and self-esteem questionnaire, in which only answers referring to self-image were considered, with 38 questions, relating to organic aspects: 1, 2, 4, 6, 22, 71; social aspects: 9, 11, 13, 25, 37, 38, 51; intellectual aspects: 17, 18, 19, 20, 21, 22, 32, 56, 57, 65; and, emotional aspects: 26, 27, 36, 55, 58, 59, 61, 62, 63, 69, 70, 72, 73, 74, 75. The score for self-image is from 37 to 185 points, from 37 to 147 points low self-image and 148 to 185 points high self-image. Approved by the Ethics and Research Committee (CEP) with opinion N* 3,313,623, after acceptance of the subjects with the ICF, data collection began. Of the 84 subjects, 19.05% were male and 80.95% were female. The result identified low self-image in 66.67% of the subjects. The calculation of self-image for the four aspects of the questionnaire scored 19.33 for the organic aspect, 25.21 for the social aspect, 34.28 for the intellectual aspect and 54.79 for the emotional aspect, resulting in 133.63 as an overall average.